2015
DOI: 10.1007/s11255-015-1085-y
|View full text |Cite
|
Sign up to set email alerts
|

Double-sling procedure for the surgical management of stress urinary incontinence with concomitant anterior vaginal wall prolapse

Abstract: Double-sling procedure is feasible, efficient, and safe. Reducing the mesh size did not have a detrimental effect on the outcomes of SUI treatment and simultaneous AVWP repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…These data matched with our results as we had cure rate of 96% based on SUI sum, according to ICIQ-SF. Also, the anatomical success rate in our study was 96%, according to POP classification similar to that found in the study by Yonguc et al [20] which was 96% in medium term follow-up with double sling procedure. This outcome was better than that was found in another study [13] in which anatomical and subjective success rates were 87.5% and 92.1%, respectively.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These data matched with our results as we had cure rate of 96% based on SUI sum, according to ICIQ-SF. Also, the anatomical success rate in our study was 96%, according to POP classification similar to that found in the study by Yonguc et al [20] which was 96% in medium term follow-up with double sling procedure. This outcome was better than that was found in another study [13] in which anatomical and subjective success rates were 87.5% and 92.1%, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…[31,32] At follow-up visits 4 (8%) patients developed dyspareunia that was improved on local estrogen cream which was in accordance with the results of Palma et al [29] who used the Nazca-Tc mesh kit and the rate of dyspareunia in their study was reportedly 2.7%. In a study by Sharifiaghdas et al [13] 68.9% of the patients who were sexually active reported improvement in their sexual function after surgery and only 6.8% of them complained of worsening of dyspareunia, similarly Yonguc et al [20] reported that their 2 patients developed dyspareunia.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Common complications include mesh extrusion, chronic pelvic pain, dyspareunia, and infection [ 7 10 ]. The anti-SUI efficacy of the prosthetic placement is barely 72–83% [ 11 13 ]; however, it is assumed that a combination of a synthetic mesh with the sling operation [ 5 , 14 16 ] will substantially increase the cure rate for concomitant SUI.…”
Section: Introductionmentioning
confidence: 99%